Distinct Microbial Communities in Dilated Cardiomyopathy Explanted Hearts Are Associated With Different Myocardial Rejection Outcomes - Pereira, Jaqueline de Jesus; Ikegami, Renata Nishiyama; Kawakami, Joyce Tiyeko; Garavelo, Shérrira Menezes; Reis, Marcia Martins; Palomino, Suely Aparecida Pinheiro; Mangini, Sandrigo; Moreno, Camila Rodrigues; Barros, Samar Freschi de; Souza, Aline Rodrigues; Higuchi, Maria de Lourdes (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Idiopathic Dilated Cardiomyopathy (IDCM) myocardial inflammation may be associated with external triggering factors such as infectious agents. Here we searched if moderate/severe heart transplantation rejection is related to the presence of myocardial inflammation in IDCM explanted hearts, associated with microbial communities. Method: Receptor myocardial samples from 18 explanted hearts were separated into groups according to post-transplant outcome: PMR (n=6) persistent moderate rejection, MR (n=7) moderate rejection that regressed after pulse therapy, and NR (n=5) no rejection/light intensity rejection. Inflammation was quantified through immunohistochemistry (IHC) and infectious agents were evaluated by immunohistochemistry (IHC), molecular biology, in situ hybridization technique, and transmission electron microscopy (TEM). Results: NR group presented lower numbers of macrophages, as well as B cells (p=0.0001) and higher HLA class II expression (p=<0.0001). PMR and MR showed higher levels of Mycoplasma pneumoniae (M. pneumoniae) (p=0.003) and hepatitis B core (p=0.0009) antigens. NR presented higher levels of PVB19 and HHV6 and a positive correlation between Borrelia burgdorferi (Bb) and enterovirus genes. Molecular biology demonstrated the presence of M. pneumoniae, Bb, HHV6 6, and Parvovirus B19 genes in all studied groups. TEM revealed structures compatible with the cited microorganisms. Conclusions: This initial study looking for infectious agents and inflammation in the IDCM explanted hearts showed that association between M. pneumoniae and hepatitis B core was associated with a worse outcome after HT, represented by MR and PMR, suggesting that different IDCM microbial community may be interfering in post-transplant myocardial rejection.